Avaliação de compostos de milho (Zea mays L.) duro resultantes de seleção recorrente recíproca, baseada em famílias de irmãos completos, entre os compostos originais dentado e duro - Vilela de Rezende, Márcio Augusto; Silva, José Carlos; Damião Cruz, Cosme; Sigueyuki Sediyama, Carlos; de Oliveira Campos, Lúcio Antônio (Revista Ceres, 2025)
Changes in grain yield and correlated characters in the Flint composites of maize originated from different cycles and variations of the reciprocal recurrent selection based on fullsib families between the original Dent and Flint composites were evaluated. The composites were also compared with commercial hybrids in different field locations.